And now, back to you - Borison, B. K. (Borison, B. K. Heartstrings (Series), 2026)
"Two competing meteorologists are forced to find common ground in this opposites attract, When Harry Met Sally inspired romance, from New York Times bestselling author B.K. Borison. Jackson Clark and Delilah Stewart have had their fair share of run-ins over the years, often ending in disaster. While Jackson thrives on routine and organization from the comfort of his radio booth, Delilah loves the spontaneity and adventure out in the field. When they're partnered against their will to cover the snowstorm of the century, they find themselves scrambling to figure out how to work together. Eager to be taken seriously as a journalist, Delilah offers Jackson a deal. If he can help her ace this assignment, she'll help him rediscover his long-lost fun side. With an undiscovered chemistry burning beneath their clashes, the unlikely partnership quickly tumbles into an easy and surprising friendship. But when other feelings start to enter the equation, can Jackson and Delilah withstand the storm? Or does what happens in the mountains, stay in the mountains?"-- Provided by publisher.